Vitamin C (L-Ascorbic Acid) Degradation Kinetics during Simultaneous Infrared Dry-Blanching and Dehydration of Apple Slices with Intermittent Heating Method - Hassan Sabbaghi (Journal of Global Pharma Technology, 2018)
Vitamin C (L-Ascorbic Acid) is the most important vitamin in nutritional terms. The polyphenols existing in apple exhibit the highest antioxidant rates hence the preservation of apples’ nutritional quality during the heating process is of a great importance. Simultaneous infrared dry blanching and dehydration (SIRDBD) based on intermittent heating method is a novel process during which the temperature is kept constant. The present study investigated the effect of irradiation temperature and the product’s thickness on polyphenol oxidase (the enzymatic browning agent) and Vitamin C degradation. For this purpose, apple slices, in different thicknesses, namely 5mm, 9mm and 13 mm, and diameter of 20 mm were prepared. Irradiation was carried out in three surface temperatures, i.e. 70, 75 and 80°C. The temperature of product center was recorded during processing. The enzymatic activity of polyphenol oxidase (PPO) and ascorbic acid content were assessed in various 2 min and 30 min intervals, respectively. Vitamin C degradation kinetics was studied. The results indicated that the enzyme degradation time was significantly lower in 80°C (P<0.05). At the time of blanching sufficiency, the center temperatures for apple slices with thicknesses of 5mm, 9mm and 13mm were 64.4, 61.7 and 60.8°C, respectively. The vitamin’s degradation kinetic constant (k) was found significantly increased with the increase in temperature or thickness (P<0.05). With the increase in thickness, the vitamin degradation was more dependent on temperature elevation (higher activation energies or Ea). Vitamin C contents were very close at the beginning of the process in different temperatures. Therefore, the high-temperature short-time approach (HTST) can, meanwhile accelerating the enzymatic inactivation, preserve the nutritional quality of the products.Keywords: Vitamin C, Blanching, Infrared, Polyphenol oxidase.